Որոշ դիտողություններ Սեֆյան Իրանի վարչական համակարգի պաշտոնների վերաբերյալ - Անահիտ Նալբանդյան (ՀՀ ԳԱԱ հրատ.)
Административные и исполнительные структуры Сефевидского Ирана были взаимосвязаны, и их деятельность являлась эффективной. В данный период существовал придворный совет мудрейших, а также должности придворных везирей, судебных руководителей и ряд других должностей. Развившись на основе уже существующей административно-правительственной структуры, административная и социальная структура Сефевидского Ирана придала новое дыхание уже существующим должностям, реконструировав и создав новые должности. В данной статье мы обратили внимание как на уже существующие государственные должности, так и на самые простые.Safavid Iran’s administrative and executive branches were interconnected and have realized very efficient activities. In those times there was a court council of wise men, court viziers, court officials and a number of other posts. Both the administrative and social systems of Safavid Iran was developped on the basis of the already existing administrative and executive modals, simultaneously improving and infusing new breath to the old posts and creating new ones as well. The posts available in Safavid Iran and their interconnection are a proof of the existence of a powerful administrative system in that period. The fact that the then governing administrative system had a considerable significance and influence on the development of todays Iran should be singled out.
Keywords: History